PENGARUH MODEL PEMBELAJARAN BERDIFERENSIASI BERBASIS KEARIFAN LOKAL TERHADAP HASIL BELAJAR BAHASA INGGRIS SISWA - Ikrimah, Ikrimah (Jurnal Pembelajaran Prospektif, 2025)
A teacher must employ an appropriate learning model in order to improve the caliber of the teaching and learning process. One learning model that teachers can employ to improve the caliber of the teaching and learning process is the differentiated learning model with the local wisdom approach. This study used a quasi-experimental methodology in conjunction with a quantitative approach. In this study, the impact of a differentiated learning strategy grounded in local wisdom on eleventh-grade students' English learning results at MAN Kota Palangka Raya is to be investigated. The alternative hypothesis (Ha), which claims that the differentiated learning model based on local wisdom has an impact on students' English achievements, is accepted in light of the findings. At the same time, the null hypothesis (H0), which claims that the differentiated learning approach based on local knowledge has no effect on students' English outcomes, is rejected. This indicates that MAN Kota Palangka Raya students' English learning outcomes can be enhanced by implementing a differentiated learning methodology based on local knowledgePENGARUH MODEL PEMBELAJARAN BERDIFERENSIASI BERBASIS KEARIFAN LOKAL TERHADAP HASIL BELAJAR BAHASA INGGRIS SISWA